EFEKTIVITAS PENGGUNAAN WHATSAPP GROUP DAN GOOGLE CLASSROOM DALAM PEMBELAJARAN JARAK JAUH (Tanjungpura University, 2021)
The Covid-19 pandemic has encouraged many schools to innovate so that they can carry out an effective learning process, including through the use of online media during PJJ. Based on this phenomenon, the research was compiled to know the effectiveness of the use of WAG media and google classroom in PJJ at MTsN 3 Serang. The research process is carried out using a survey method with a descriptive approach that focuses on evaluating the learning process that has been taking place. Respondents involved in the study were 30 people who were students of class IX F. Data was collected using a questionnaire instrument. The data analysis process was carried out using a descriptive statistical approach with data presented in the form of diagrams and descriptive narratives. The results of the study found that students considered that using WAG and Google Classroom media, distance learning could be carried out. According to respondents, for distance learning to run more effectively, teachers need to 1) conduct learning with video calls such as Gmeet / Zoom meeting, 2) provide material that is concise and easy to understand, 3) provide material before giving assignments, 4) give assignments that are following the material presented, and 5) does not impose tasks on students.